(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article is dedicated to the topology of formants of Guliapole surnames (on the materials of anthroponomy dictionary written by the professor V.O. Gorpynych). The most wide-spread suffixes of surnames are analyzed. The frequency of their usage, combinability with bases, spreading on the territory under study is also examined.